The good gut diet cookbook with prebiotics and probiotics - Humphries, Carolyn (Lorenz Books, 2016)
This book focuses on eating certain foods as part of a normal, healthy diet, to help improve the digestive system. Eating higher levels of fibre, naturally fermented foods and those that contain probiotics or prebiotics means that good bacteria is encouraged to grow in the gut, leading to waste products being eliminated more efficiently. A helpful and clearly explained introduction sets out what foods should be eaten and how to add quick-fix pre- and probiotic foods to your meals. The book also offers a two-week eating plan and recipes for dishes that are packed with the right foods to balance your diet. Increase beneficial bacteria for optimum gut health, and improve your digestion and well-being with naturally fermented foods. Make your own pantry of probiotic goodness: pickled vegetables, kimchi, sauerkraut and sourdough. The book offers help and advice on how to improve digestion, detox naturally, counteract bloating, reduce cholesterol, and reach and maintain the correct weight. Contains 80 recipes and ideas, together with food lists and an eating plan, to help alleviate the symptoms of diarrhoea, constipation, IBS, coeliac disease and diabetes.--Provided by publisher.